2021
DOI: 10.1155/2021/1292921
|View full text |Cite|
|
Sign up to set email alerts
|

Predictive Value of MPV and Plasma NT-ProBNP Combined with the Simplified Geneva Scale for the Prognosis of Acute Pulmonary Embolism

Abstract: Objective. To explore the predictive value of mean platelet volume (MPV) and plasma N-terminal probrain natriuretic peptide (NT-ProBNP) combined with a simplified Geneva scale for the prognosis of acute pulmonary embolism (APE). Methods. The clinical data of 68 patients with APE admitted to our hospital from October 2017 to October 2019 were collected. According to the prognosis, the patients were divided into a good prognosis group (n = 45) and a poor prognosis group (n = 23). The clinical data, laboratory cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The role of platelet indices (platelet counts and MPV) as marker of severity of aPE is still controversial. The increase in platelet size is associated with increased adhesiveness and this association seems to find its clinical confirmation by some studies which showed a correlation between elevated MPV and severity of aPE [ 9 , 20 , 21 ]. However, other studies showed that a single MPV dosage at aPE diagnosis did not correlate with aPE severity [ 22 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The role of platelet indices (platelet counts and MPV) as marker of severity of aPE is still controversial. The increase in platelet size is associated with increased adhesiveness and this association seems to find its clinical confirmation by some studies which showed a correlation between elevated MPV and severity of aPE [ 9 , 20 , 21 ]. However, other studies showed that a single MPV dosage at aPE diagnosis did not correlate with aPE severity [ 22 ].…”
Section: Discussionmentioning
confidence: 79%
“…As a matter of fact, they were both associated with short and long term mortality in aPE [ 7 ]. Moreover, some promising results showed that mean platelet volume (MPV) correlated with diagnosis of deep venous thrombosis (DVT) and prognosis of aPE [ 8 , 9 ]. On the other hand, the role of CBC parameters for the prediction of aPE diagnosis and evolution in patients affected by severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) infection is still unclear [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The indications for a kidney biopsy at our institution were T2DM and kidney damage, especially in T2DM patients without diabetic retinopathy, with sudden onset overt proteinuria, with obvious glomerular hematuria, or with rapidly declining kidney function [ 12 ]. Patients with coexisting nondiabetic kidney diseases (such as membranous and IgA nephropathy, systemic lupus erythematosus, ANCA-associated vasculitis), T1DM, acute cardiovascular events (such as hospitalization for heart failure, myocardial infarction, and stroke within three months before kidney biopsy) [ 13 ], acute pulmonary embolism [ 14 ], acute kidney injury [ 15 ], urosepsis [ 16 ], progression to ESKD before kidney biopsy, and patients without baseline serum NT-proBNP level information were excluded ( Figure 1 ). All patients provided written informed consent, and this study was approved by the institutional review board at the West China Hospital of Sichuan University.…”
Section: Methodsmentioning
confidence: 99%
“…Among influenza pneumonia patients, the change of MVP strongly predicts acute respiratory distress syndrome [ 9 ]. It was also reported that higher MPV was an independent risk factors for the poor prognosis of patients with acute pulmonary embolism [ 10 ]. Among some patients with surgery, MPV values were significantly higher in the non-survivors following acute abdominal surgery [ 11 ], and patients with increased MPV showed lower rates of 1-year survival following undergoing cytoreductive surgery with hyperthermic intraperitoneal chemotherapy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%